Sample Sizes for Clinical, Laboratory and Epidemiology Studies. - Machin, David (John Wiley & Sons, Incorporated, 2018)
"Sample Size Tables for Clinical Studies provides the statistical tools - equations, formulae and numerical tables - statisticians and researchers need to design and plan valid clinical studies and to accurately analyse publishable results. It explains the sample size considerations that are important when designing and planning any type of clinical study. It clearly outlines the methodologies employed, within the context of clinical studies and trials, and provides relevant practical examples. Each chapter provides and explains sets of sample size tables. They also include Bibliography and References sections directed towards further guidance on the principles discussed and more detailed explanations"--Provided by publisher.